The Effect Of Foreign Direct Investment (Fdi), Trade Openness, Exports And Inflation On Indonesia's Economic Growth In The 2015-2024 Period - Widya Intan Sari; Denok Sunarsi; Kharisma Danang Yuangga (Transforma Jurnal Manajemen, 2026)
The purpose of this study is to determine the effect of Foreign Direct Investment, Trade Openness, exports, and inflation on Economic Growth 2015-2024 partially or simultaneously. The method used in this study is quantitative. Data analysis uses classical assumption tests, regression analysis, coefficient of determination analysis, and hypothesis testing using Eviews 13. From the results of the data analysis, it can be concluded that the variables of Foreign Direct Investment, Trade Openness, exports, and inflation do not have a partial effect on Economic Growth. Simultaneously, it also shows that there is no influence between Foreign Direct Investment, Trade Openness, exports, and inflation on Economic Growth. This is proven by the test obtained value0.2038> 0.05. This can also be seen from the Adj R Square of 0.3494, which means that the variables Foreign Direct Investment, Trade Openness, and Exports have a contribution of 34.94%, while 65.06% is influenced by other variables not explained in this study.